Parental pre-pregnancy body mass index and risk of low birth weight in offspring: A prospective cohort study in central China - Jianhui Wei; Tingting Wang; Tingting Wang; Jing Shu; Yiping Liu; Xinli Song; Mengting Sun; Taowei Zhong; Qian Chen; Manjun Luo; Senmao Zhang; Peng Huang; et al. (Frontiers Media S.A., 2022)
BackgroundLow birth weight (LBW) is one of the most common adverse pregnancy outcomes. Previous studies have consistently shown that maternal body mass index (BMI) status before and during pregnancy is associated with LBW. However, previous studies lacked an association between paternal BMI and the conjunction effect of a couple's BMI and LBW in the offspring. Therefore, we established a cohort of pre-pregnancy couples to prospectively assess the relationship between maternal and paternal pre-pregnancy BMI and offspring LBW, very low birth weight (VLBW), and extremely low birth weight (ELBW).MethodsA prospective cohort study was established in Central China. A total of 34,104 pregnant women with singleton pregnancies at 8-14 gestational weeks and their husbands were finally enrolled and followed to 3 months postpartum. The multivariate logistic regression and restrictive cubic spline model were used to explore the relationship between parental pre-pregnancy BMI and the risk of LBW, VLBW, and ELBW in offspring.ResultsOf the 34,104 participants, maternal pre-pregnancy overweight and obesity were associated with a higher risk of LBW (overweight: OR = 1.720, 95% CI = 1.533 ~ 1.930; obesity: OR = 1.710, 95% CI = 1.360 ~ 2.151), VLBW (overweight: OR = 2.283, 95% CI = 1.839 ~ 2.834; obesity: OR = 4.023, 95% CI = 2.855 ~ 5.670), and ELBW (overweight: OR = 3.292, 95% CI = 2.151 ~ 5.036; obesity: OR = 3.467, 95% CI = 1.481 ~ 8.115), while underweight was associated with a higher risk of LBW (OR = 1.438, 95% CI = 1.294 ~ 1.599) and a lower risk of ELBW (OR = 0.473, 95% CI = 0.236 ~ 0.946). Paternal pre-pregnancy overweight and obesity were associated with a higher risk of LBW (overweight: OR = 1.637, 95% CI = 1.501 ~ 1.784; obesity: OR = 1.454, 95% CI = 1.289 ~ 1.641) and VLBW (overweight: OR = 1.310, 95% CI = 1.097 ~ 1.564; obesity: OR = 1.320, 95% CI = 1.037 ~ 1.681), while underweight was associated with a lower risk of LBW (OR = 0.660, 95% CI = 0.519 ~ 0.839). Parents who were both excessive-weights in pre-pregnancy BMI, as well as overweight mothers and normal-weight fathers before pre-pregnancy, were more likely to have offspring with LBW, VLBW, and ELBW. Dose-response relationship existed between parental pre-pregnancy and LBW, VLBW, and ELBW, except for paternal BMI and ELBW.ConclusionsParental pre-pregnancy BMI was associated with the risk of LBW in offspring. Management of weight before pregnancy for couples might help reduce their adverse pregnancy outcomes in future intervention studies.